2021
DOI: 10.1186/s12891-021-04231-7
|View full text |Cite
|
Sign up to set email alerts
|

Low serum vitamin B12 levels are associated with degenerative rotator cuff tear

Abstract: Background Vitamin B12 (Vit B12) deficiency results in elevated homocysteine levels and interference with collagen cross-linking, which may affect tendon integrity. The purpose of this study was to investigate whether serum Vit B12 levels were correlated with degenerative rotator cuff (RC) tear. Methods Eighty-seven consecutive patients with or without degenerative RC tear were enrolled as study participants. Possible risk factors (age, sex, medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…These results align with a recent systematic review that showed an association between metabolic syndrome and RCD [8]. In Kim et al's (2021) study, significantly lower levels of vitamin B12, vitamin D, and phosphorus were found in serum samples of patients with RCD compared with control group patients [53]. In addition, the higher vitamin D levels were calculated to have a significantly lower odds ratio (0.89, 95% CI 08.…”
Section: Discussionsupporting
confidence: 84%
“…These results align with a recent systematic review that showed an association between metabolic syndrome and RCD [8]. In Kim et al's (2021) study, significantly lower levels of vitamin B12, vitamin D, and phosphorus were found in serum samples of patients with RCD compared with control group patients [53]. In addition, the higher vitamin D levels were calculated to have a significantly lower odds ratio (0.89, 95% CI 08.…”
Section: Discussionsupporting
confidence: 84%
“…Considering shoulder pain may be associated with infection, immune ( 16 ), diabetes mellitus ( 34 ) and bone metabolism ( 14 , 35 ), we collected related routine blood examination data, including leukocyte count, percentage of neutrophils, C-reactive protein (CRP), serum amyloid protein A (SAA), erythrocyte sedimentation rate (ESR), Vitamin D3, glycosylated hemoglobin (HbA1c), fasting plasma glucose (FPG) and 2-h postprandial plasma glucose (P2hPG) ( 28 ) to test their relationship with shoulder pain. Some patients underwent shoulder joint ultrasonography during hospitalization to assess the long head of biceps tendon, supraspinatus tendon, and subacrominal-subdeltoid (SA-SD) bursae of both shoulders, which helped to analyze the cause of shoulder pain.…”
Section: Methodsmentioning
confidence: 99%
“…Neurological factors include soft paralysis ( 9 ), spasm, brachial plexus injury, complex regional pain syndrome (CRPS) ( 10 ), central sensitization ( 11 ), paresthesia ( 12 ), unilateral neglect, etc. Recent studies have found that other factors, such as diabetes mellitus ( 13 ), vitamin D3 deficiency ( 14 ), psychology ( 15 ) and immunity ( 16 ), may also be associated with HSP.…”
Section: Introductionmentioning
confidence: 99%
“…tendon integrity (13). Chi et al found that Vitamin B12, vitamin D and angiopoietin are significantly reduced in tendon disorders, which may contribute to a better understanding of the complex pathology of tendon disorders (54).…”
Section: B Amentioning
confidence: 99%
“…In a mouse model, vitamin D (VitD) prevented local decrease in bone mineral density (increased roughness of the proximal humerus) and improved rotator cuff tendon healing (12). Low serum vitamin B12 levels are associated with degenerative rotator cuff tear (13). In addition, leucine ameliorated tenotomy-induced muscle atrophy by inhibiting autophagy and possibly activating the PI3K/AKT/mTOR pathway in rotator cuff injury (14).…”
Section: Introductionmentioning
confidence: 99%